Past, Present and Future of the Thessaloniki Olympic Museum. Role and Mission in today’s museum world. - Τρυφωνόπουλος, Πέτρος (Πανεπιστήμιο Πελοποννήσου, 2013)
This master thesis, starting from the debate on socio-cultural meanings of museum objects and the museum’s historical background, raises the main issues that all museums today and in particular those that the Thessaloniki Olympic Museum has to face in order to keep up with the constant changes in present-day society. Over the past years a great debate on the nature of the institution of museums as educational centers has been launched. The scientific concern that these studies have caused can be seen in the abundant publications, articles, books and surveys that deal with the educational role of the museum and its outcomes. These considerations have attributed to museums great relevance regarding their societal and economical relations alike. Our work will focus on the socio-educational aspect of the museums and more specifically of the Olympic Museum in Thessaloniki. The approach of this study firstly follows the path of the general to specific logic. The rules of deductive reasoning are followed by presenting the general characteristics of museums and then the specific features of the Thessaloniki Olympic Museum. Nevertheless, as soon as our showcase is presented, our conclusions are based on both deductive and inclusive reasoning. Our argumentation is reached from both specific examples, that the Olympic Museum of Thessaloniki offers, and general statements from other Western museums. Our study’s framework is starting from the analysis of the museological reality to the implication of the science of education into the pedagogical programs that are developed by museums educators of the Thessaloniki Olympic Museum. The goal of this thesis is to discuss the development of educational and other operational strategies embodied into the mission and policy of the museum in question. Ultimately, the relevance of this discussion will demonstrate that the technological evolution within a post-modern museum such as the Olympic Museum has altered the nature of the museum or is about to change it in the near future. The Olympic Museum of Thessaloniki provides a vehicle by which museums as social and media servants can reach diverse audiences through the promotion of Olympic and universal values.
Keywords: Olympic Museum of Thessaloniki; Sports museums; Olympism; Museums - Educational aspects; Ολυμπιακό Μουσείο Θεσσαλονίκης; Αθλητικά μουσεία; Ολυμπισμός; Μουσεία - Εκπαιδευτικές απόψεις; Olympic Museum of Thessaloniki; Museums; Education; Programs; Networking; Collaborations; Strategic Planning; Ολυμπιακό Μουσείο Θεσσαλονίκης; Μουσεία; Εκπαίδευση; Προγράμματα; Δικτύωση; Συνεργασίες; Στρατηγικός Σχεδιασμός